THE SOUTH CHINA SEA DISPUTE AND SINO-VIETNAMESE RECONCILIATION (Journal of International Studies, 2023)
This article attempts to analyse the South China Sea (SCS) conflict from the standpoints of both Vietnam and China. The paper discusses the factors that contributed to the recent escalation of the Vietnam-China conflict, the implications of the competition for Vietnam and other regions of interest, including the People’s Republic of China and the United States, and the potentially desirable Association of Southeast Asian Nations (ASEAN) solutions. The research method was based on reviews of recent reports and surveys published in newspapers or think tanks. This qualitative analysis elucidates and deepens our understanding of the SCS dispute. The research is significant because it sheds light on the issues at stake, particularly from the perspective of Vietnam, an ASEAN member. With this in mind, the hope is that academics and stakeholders can make the best possible use of the data, various arguments, and analyses presented to advance knowledge through correction and further research. To resolve this issue, the study concluded that China and Vietnam must meet and discuss it. The United States’ involvement in this maritime dispute complicates an already complex situation.